Development of eco-tourism strategy using swot analysis: case study of Bayung Gede village - Putra, E P; Nasution, A H (IPTEK Journal of Proceedings Series, 2018)
Bayung Gede Village is one chosen village to be developed as tourism village. However, due to observation result conducted by researcher, Bayung Gede village still has no tourism village development strategy design. This research aims to formulate appropriate strategy to be implemented in Bayung Gede village. Strategy formulation based on SWOT-4K matrices and performed by using TOWS matrices. From the research result, found that Bayung Gede village is in prime condition to expand its market and to develop product also has a lot of opportunities which can be utilized to develop tourism village. By development of Bayung Gede village to be tourism village, it would be able to increase village revenue and welfare.